2020
DOI: 10.1111/sms.13891
|View full text |Cite
|
Sign up to set email alerts
|

Maternal body mass index, change in weight status from childhood to late adulthood and physical activity in older age

Abstract: This study aimed to examine the longitudinal associations of maternal body mass index (BMI), weight status in childhood and late adulthood and device‐measured total physical activity (TPA) in older age. The study involves 552 participants from Helsinki Birth Cohort Study who were born in Helsinki, Finland, in 1934‐1944. TPA was measured with a multisensory body monitor at a mean age of 70 years and expressed in metabolic equivalent of task hours/day (METh/d). Childhood overweight (BMI > 85th percentile) was ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Given potential interrelationships between early-life factors, for example, between size at birth and gestational age, and between maternal BMI and birth weight, models including body size at birth were also adjusted for gestational age and maternal BMI models additionally for birth weight. Interactions between exposure variables and sex on FI were also tested given previously observed sex-depended associations of early-life factors (4,5,(21)(22)(23). We observed a significant sex interaction only in the model of temporary wartime separation as exposure variable, where also the 3-way interaction of sex * age * separation status was added to the model.…”
Section: Methodsmentioning
confidence: 81%
See 2 more Smart Citations
“…Given potential interrelationships between early-life factors, for example, between size at birth and gestational age, and between maternal BMI and birth weight, models including body size at birth were also adjusted for gestational age and maternal BMI models additionally for birth weight. Interactions between exposure variables and sex on FI were also tested given previously observed sex-depended associations of early-life factors (4,5,(21)(22)(23). We observed a significant sex interaction only in the model of temporary wartime separation as exposure variable, where also the 3-way interaction of sex * age * separation status was added to the model.…”
Section: Methodsmentioning
confidence: 81%
“…A higher maternal BMI has been associated with poorer offspring physical and mental functioning in the sixth decade of life in men ( 22 ). The U-shaped association between maternal BMI and offspring total physical activity in the sixth decade was observed only among women ( 23 ). However, we observed no sex difference regarding the rate of change in frailty in the present study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…By and large, it has been found that as they age, subjects' BMIs increase, and this measure is accepted as a tool for diagnosing issues related to obesity, the potential progression of diseases, and health in general [48]. This finding could be due to the changes that take place during adulthood, including changing eating habits-namely an increased intake of saturated fats-as well as the availability of technological resources that lead to a reduction in the practice of physical activities and thus an increase in BMI [49].…”
Section: Discussionmentioning
confidence: 99%